Unlocking Value: Exploring the Interplay of Intellectual Capital, Corporate Governance, Corporate Social Responsibility, and Profitability in Business Success - Nasution, Mutiah; Sadalia, Isfenti; Irawati, Nisrul; Ilham, Rico Nur (International Journal of Business, Economics & Financial Studies, 2023)
Globalization has contributed to shifts in business practices and changes in the business environment in all industrial sectors. Many existing and developing companies face great competition domestically and globally. This causes companies to have to compete by continuously maintaining their business. This study determines the effect of intellectual capital, good corporate governance, and corporate social responsibility on firm value, with profitability as an intervening variable. This research uses secondary data, the publications of the Indonesia Stock Exchange and the Malaysia Stock Exchange, reference books, journals, research results, and data retrieved from the internet related to the research topic. The data analysis method is a statistical method assisted by the Smart PLS program. The results show that VAIC (X1) had a positive and significant direction on the profitability (ROA) variable both in Indonesia and Malaysia, GCG (X2) had a positive and significant direction on the profitability (ROA) variable in Indonesia but positive direction though insignificant direction on the Profitability variable in Malaysia, CSR (X3) had a positive but insignificant effect on the profitability (ROA) variable in Indonesia and Malaysia, and VAIC (X1) had a positive but insignificant effect on Firm Value.